2022
DOI: 10.3390/aerospace9020052
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Material Selection on Aviation Sustainability, from a Circular Economy Perspective

Abstract: Climate change and global warming pose great sustainability challenges to the aviation industry. Alternatives to petroleum-based fuels (hydrogen, natural gas, etc.) have emerged as promising aviation fuels for future aircraft. The present study aimed to contribute to the understanding of the impact of material selection on aviation sustainability, accounting for the type of fuel implemented and circular economy aspects. In this context, a decision support tool was introduced to aid decision-makers and relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…At the same time, most companies actively pursuing CE practices are phasing out plastics and transitioning to more environmentally friendly materials. In this way, the companies grant that if the packaging cannot be recycled due to strict regulations, contamination will be minimal compared to plastic (Markatos & Pantelakis, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, most companies actively pursuing CE practices are phasing out plastics and transitioning to more environmentally friendly materials. In this way, the companies grant that if the packaging cannot be recycled due to strict regulations, contamination will be minimal compared to plastic (Markatos & Pantelakis, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Concretely, the initiatives added are the availability of booking systems to predict the number of meals needed and the composition of edibles packaging. All these activities are important CE initiatives explicitly linked to the airlines industry (ICAO, 2014; Markatos & Pantelakis, 2022)…”
Section: Methodsmentioning
confidence: 99%
“…There are also approaches that combine assessment methods to assess CE. Markatos and Pantelakis [42] introduced a decision support tool that combines life-cycle-based metrics encompassing ecological and economic aspects and a circular economy indicator (CEI) centered on material/component attributes. This CEI is associated with quality characteristics and accommodates the decline in the quality of materials through multiple recycling loops.…”
Section: Assessment Of the Cementioning
confidence: 99%
“…They concluded that materials should be recycled to attain this objective. Markatos and Pantelakis [21] assessed aviation sustainability based on circular economy principles and concluded that the recycling of materials plays a critical role in this context.…”
Section: Literature Reviewmentioning
confidence: 99%